2020
DOI: 10.1136/flgastro-2019-101288
|View full text |Cite
|
Sign up to set email alerts
|

Steroid use and misuse: a key performance indicator in the management of IBD

Abstract: Corticosteroids remain an important tool for inducing remission in inflammatory bowel disease (IBD) but they have no role in maintenance of remission. The significant adverse side effect profile of these drugs means their use should be avoided where possible or measures taken to reduce their risk. Despite an expanding array of alternative therapies, corticosteroid dependency and excess remain common. Appropriate steroid use is now regarded a key performance indicator in the management of IBD. This article aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 86 publications
1
13
0
2
Order By: Relevance
“…Despite this fact, it has been documented that one in eight patients with UC and one in four patients with CD in the United Kingdom experience chronic steroid use of greater than 6 months. This was also found to be true in Europe, Canada, and the United States within the first 5 years of diagnosis 9 . Our study revealed that patients with chronic steroid use had an increased risk of thrombotic events, osteoporosis, and opportunistic infections.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Despite this fact, it has been documented that one in eight patients with UC and one in four patients with CD in the United Kingdom experience chronic steroid use of greater than 6 months. This was also found to be true in Europe, Canada, and the United States within the first 5 years of diagnosis 9 . Our study revealed that patients with chronic steroid use had an increased risk of thrombotic events, osteoporosis, and opportunistic infections.…”
Section: Discussionsupporting
confidence: 74%
“…This was also found to be true in Europe, Canada, and the United States within the first 5 years of diagnosis. 9 Our study revealed that patients with chronic steroid use had an increased risk of thrombotic events, osteoporosis, and opportunistic infections. The cause for the prothrombotic state in IBD appears to be due to local or systemic inflammation and is dependent on disease severity.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Truelove y Witts fueron los primeros en probar la cortisona, conocida como «las tabletas especiales», para inducir la remisión en la CU. Dos tercios de los pacientes en el grupo de tratamiento mejoraron o entraron en remisión clínica completa, en comparación con aproximadamente un tercio de los tratados con la terapia médica estándar de la época 33,34 . Por lo anterior comentado, el pionero de los ensayos clínicos controlados en la EII fue Sidney Charles Truelove, quien en 1955 publicó el primero de ellos realizado sobre la eficacia de los glucocorticoides en la CU grave.…”
Section: Glucocorticoidesunclassified
“…Se informó de que los glucocorticoides posteriores eran eficaces para la inducción de la remisión en la enfermedad de Crohn, y tres cuartas partes de los pacientes mejoraron inicialmente. Sin embargo, se hizo evidente que los beneficios a largo plazo de los glucocorticoides para los pacientes con EII eran menos favorables y estaban asociados con una amplia gama de efectos secundarios significativos 33 . En 1979, Summers y sus colaboradores informaron de que la prednisolona oral, a partir de 60 mg una vez al día, fue eficaz para inducir la remisión en pacientes con enfermedad de Crohn activa 14 .…”
Section: Glucocorticoidesunclassified